2014
DOI: 10.1016/j.jpain.2014.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Exercise-Induced Hypoalgesia

Abstract: The purpose of this study was to examine opioid and endocannabinoid mechanisms of exercise-induced hypoalgesia (EIH). Fifty-eight men and women (mean age = 21 yrs) completed three sessions. During the first session, participants were familiarized with the temporal summation of heat pain and pressure pain protocols. In the exercise sessions, following double-blind administration of either an opioid antagonist (50 mg naltrexone) or placebo, participants rated the intensity of heat pulses and indicated their pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
232
3
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 288 publications
(277 citation statements)
references
References 69 publications
7
232
3
6
Order By: Relevance
“…12 Furthermore, a recent human study suggested the involvement of a non-opioid vs. opioid mechanism in isometric EIH using temporal summation and PPTs as the experimental pain tests. 21 Greater EIH was associated with increased circulating levels of the endocannabinoid docosahexaenoylethanolamine (DHA) following isometric exercise. Interestingly, DHA deficiency is associated with aging 1 , however age-related differences in the DHA response to exercise is not known.…”
Section: Discussionmentioning
confidence: 99%
“…12 Furthermore, a recent human study suggested the involvement of a non-opioid vs. opioid mechanism in isometric EIH using temporal summation and PPTs as the experimental pain tests. 21 Greater EIH was associated with increased circulating levels of the endocannabinoid docosahexaenoylethanolamine (DHA) following isometric exercise. Interestingly, DHA deficiency is associated with aging 1 , however age-related differences in the DHA response to exercise is not known.…”
Section: Discussionmentioning
confidence: 99%
“…The authors speculated that activation of the endogenous opioid system by exercise may have alleviated withdrawal and provided a superior psychobiological substitute for those who used heroin compared to those who used tobacco or alcohol, which primarily affect non-opioid (e.g., acetylcholinergic and GABAergic) pathways (19). Along a similar vein, exercise interventions conducted with CUD patients and which include investigation of a psychobiological mechanism are an appropriate and intriguing next area of research, as exercise has been shown to repeatedly and robustly activate the endocannabinoid (eCB) system in healthy individuals (27–32). …”
Section: Exercise In the Treatment Of Cannabis Use Disordermentioning
confidence: 99%
“…For healthy individuals, acute bouts of exercise tend to reduce pain sensitivity (i.e., create hypoalgesia) through the release of endogenous opioids, which have been proposed to help modulate pain processing in areas of the brain and spinal cord. Therefore, exercise is generally expected to result in higher pain tolerance and reduced pain [11]. However, in patients with chronic pain, acute aerobic and isometric exercise may actually have the opposite (hyperalgesic) effect; in other words, pain sensitivity may increase immediately following exercise [12].…”
Section: What Is the Evidence Behind Exercise Recommendations For Jfm?mentioning
confidence: 99%